Optimising strategies to address mental ill-health in doctors and medical students: ‘Care Under Pressure’ realist review and implementation guidance - Carrieri, D; Mattick, K; Pearson, M; Papoutsi, C; Briscoe, S; Wong, G; Jackson, M (Springer Nature, 2020)
Background: Mental ill-health in health professionals, including doctors, is a global and growing concern. The existing literature on interventions that offer support, advice and/or treatment to sick doctors has not yet been synthesised in a way that considers the complexity and heterogeneity of the interventions, and the many dimensions of the problem. We (1) reviewed interventions to tackle doctors’ and medical students’ mental ill-health and its impacts on the clinical workforce and patient care—drawing on diverse literature sources and engaging iteratively with diverse stakeholder perspectives—and (2) produced recommendations that support the tailoring, implementation, monitoring and evaluation of contextually sensitive strategies to tackle mental ill-health and its impacts.